CLEC11A-Driven Molecular Mechanisms in Intervertebral Disc Degeneration: A Comprehensive Multi-Omics Study - Jiang N; Wang Q; Hu Z; Tian X (Journal of Inflammation Research)
Nizhou Jiang,1,* Quanxiang Wang,2,* Zhenxin Hu,3,* Xiliang Tian1 1Department of Spine Surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 2Department of Otolaryngology-Head and Neck Surgery, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 3Department of Spine Surgery, Peking University Fourth School of Clinical Medicine, Beijing Jishuitan Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiliang Tian, Department of Spine Surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China, Email tianxiliang1983@163.comBackground: Intervertebral disc degeneration (IVDD) is a common chronic degenerative disease with a complex etiology involving genetic and environmental factors. However, the genetic pathogenesis and key driving factors of IVDD remain largely unknown.Methods: In this study, we combined MR with transcriptomic sequencing to identify key pathogenic genes implicated in IVDD. Further exploration using single-cell transcriptomics elucidated the specific cell types and pathways through which these genes modulate IVDD. Mediational MR analysis provided insights into the intermediary roles of 91 inflammatory factors and serum metabolites in the genetic causation pathway of IVDD. Finally, we validated these findings through in vitro experiments, confirming the regulatory roles of these critical genes in the progression of IVDD.Results: Transcriptomic and MR analyses identified six candidate pathogenic genes (AEN, CLEC11A, HMGN1, LRRC25, TAF7, and TREM1) significantly associated with IVDD. Subsequent single-cell analysis suggested that CLEC11A, TREM1, and HMGN1 may play pivotal roles in IVDD progression by modulating chondrocyte function and inflammatory responses. Mediation MR analysis further indicated that CLEC11A might significantly elevate IVDD risk by upregulating the inflammatory mediator ARTN and the uncharacterized serum metabolites X-12731 and X-18901 (ARTN: OR=1.078, 95% CI: 1.004– 1.158, P=0.038; X-12731: OR=0.906, 95% CI: 0.852– 0.960, P=0.043; X-18901: OR=1.090, 95% CI: 1.007– 1.179, P=0.034). In vitro experiments demonstrated that overexpression of CLEC11A in nucleus pulposus cells significantly enhanced mRNA and protein expression of IVDD-related inflammatory markers; conversely, silencing CLEC11A markedly reduced these expressions. Similarly, overexpression of ARTN significantly increased, while knockdown decreased, the expression of these inflammatory markers in nucleus pulposus cells.Conclusion: Our integrative multi-omics analysis indicates that CLEC11A exacerbates IVDD by upregulating ARTN and inducing metabolic dysregulation, thereby amplifying the inflammatory pathways that drive disease progression. Keywords: intervertebral disc degeneration, Mendelian randomization, mediated Mendelian randomization, inflammatory factors, serum metabolites, single-cell sequencing